2019
DOI: 10.30802/aalas-cm-19-000004
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pain and Analgesia in Rodent Models of Sepsis

Abstract: Sepsis is a multifaceted host response to infection that dramatically affects patient outcomes and the cost of health care. Animal models are necessary to replicate the complexity and heterogeneity of clinical sepsis. However, these models entail a high risk of pain and distress due to tissue trauma, inflammation, endotoxin-mediated hyperalgesia, and other mechanisms. Several recent studies and initiatives address the need to improve the welfare of animals through analgesics and standardize the models used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…To be specific, SAE may cause long-term neurological deficits, with 10-20% of patients in septic shock showing cognitive deficits, 10-30% of them showing anxiety and stress disorders, and 31-70% of patients having chronic pain. In addition, SAE may result in epileptic seizures, delirium, mild or deep unconsciousness, and even coma (11)(12)(13).…”
Section: Clinical Symptoms Of Saementioning
confidence: 99%
“…To be specific, SAE may cause long-term neurological deficits, with 10-20% of patients in septic shock showing cognitive deficits, 10-30% of them showing anxiety and stress disorders, and 31-70% of patients having chronic pain. In addition, SAE may result in epileptic seizures, delirium, mild or deep unconsciousness, and even coma (11)(12)(13).…”
Section: Clinical Symptoms Of Saementioning
confidence: 99%
“…This has led to low consumption of analgesics in septic model studies. In fact, only 15% of studies that used the septic model reported using analgesics [ 174 , 175 ]. This concern may be truly related to NSAIDs and morphine that can elevate the level of circulating IL-6.…”
Section: Maintenancementioning
confidence: 99%
“…This concern may be truly related to NSAIDs and morphine that can elevate the level of circulating IL-6. However, other opioid analgesics such as buprenorphine have low side effects and immunosuppressive activity and should be used to control the pain [ 174 , 176 , 177 ]. Buprenorphine can be used subcutaneously, immediately before induction of the model, and then every 12 h for at least two days [ 169 , 174 ].…”
Section: Maintenancementioning
confidence: 99%
“…Chronic pain is a frequently reported consequence of critical care illnesses, with 31-70% of septic patients claiming pain 6 months after discharge from the hospital (Carpenter et al, 2019). The most likely cause of this pain can be inflammation, and microglia are believed to contribute to this pathology.…”
Section: Activated Microglia In Sepsis-associated Chronic Painmentioning
confidence: 99%
“…To be specific, it has been demonstrated that SAE can cause long-term neurological deficits, including cognitive deficits (10-20%) and anxiety and stress disorders (10-30%) (Iwashyna et al, 2010;Battle et al, 2013;Helbing et al, 2018). Moreover, 31-70% of sepsis survivors claim to suffer from pain 6 months after discharge from the hospital (Carpenter et al, 2019). Given that there is still a lack of specific treatment options proposed for SAE and sepsis-associated chronic pain, understanding the mechanisms of the pathological alterations in the brain is essential for developing effective treatments to avoid the potentially devasting effects of sepsis.…”
Section: Introductionmentioning
confidence: 99%